جريمة تهريب المهاجرين في التشريع الجزائري و آليات مكافحتها - عنيبي بشسى - - لعويجي إيمان (المسيلة, 2023)
تعد جريمة تيريب المياجرين من المشاكل التي فرضت نفسيا عمى الساحة الدولية, حيث أنيا من أىم أنماط اإلجرام المنظم, وىذا الرتباطيا بالمستجدات العصرية التي تطورت مستعممة طرق وأساليب حديثة لمتحايل عمى القانون والتممص منو بشتى الوسائل, مما جعل المجتمع الدولي يتحرك لمحاربة ىذه الظاىرة الخطيرة ضمن اتفاقيات دولية تجعل الدول وانشاء أجيزة لمكافحتيا في إطار سياسة وقائية األطراف تعمل عمى وضع تشريعات داخمية, ردعية. والجزائر بسبب موقعيا الجغرافي الذي يجعميا دولة عبور لتيريب المياجرين وادراكا منيا لخطورة ىاتو الجريمة, سارعت لمتوقيع عمى االتفاقية والبروتوكول اإلضافي وتكييف القوانين الوطنية وتسخير آليات من أجل محاربة ىاتو الجريمة. Summary: The crime of migrant smuggling is one of the problems that has imposed itself on the international scene, as it is one of the most significant forms of organized crime. This is due to its connection to modern developments, which have evolved by using new methods and techniques to circumvent and evade the law in various ways. As a result, the international community has taken action to combat this dangerous phenomenon through international agreements that require participating countries to establish internal legislation and establish institutions to fight against it within a preventive and deterrent policy. Algeria, due to its geographical location, which makes it a transit country for migrant smuggling, and its awareness of the seriousness of this crime, has quickly signed the convention and the additional protocol, adapted national laws, and mobilized mechanisms to combat this crime.
Keywords: جريمة تهريب المهاجرين - التشريع الجزائري - آليات مكافحتها